KINETIC EVALUATION OF ETHANOL-TOLERANT THERMOPHILE Geobacillus thermoglucosidasius M10EXG FOR ETHANOL PRODUCTION - Riyanti, Eny Ida; Rogers, Peter L. (Indonesian Agency for Agricultural Research and Development - MOA, 2009)
Thermophiles are challenging to be studied for ethanol productionusing agricultural waste containing lignocellulosic materials richin hexose and pentose. These bacteria have many advantagessuch as utilizing a wide range of substrates, including pentose (C5)and hexose (C6). In ethanol production, it is important to useethanol tolerant strain capable in converting lignocellulosichydrolysate. This study was aimed to investigate the growth profileof ethanol-tolerant thermophile Geobacillus thermoglucosidasiusM10EXG using a defined growth medium consisted of single carbonglucose (TGTV), xylose (TXTV), and a mixture of glucose andxylose (TGXTV), together with the effect of yeast extract additionto the media. The experiments were conducted at the Schoolof Biotechnology and Biomolecular Sciences of The Universityof New South Wales, Australia on a shake flask fermentationat 60Â°C in duplicate experiment. Cultures were sampled everytwo hours and analised for their kinetic parameters includingthe maximum specific growth rate (Âµmax), biomass yield (Yx/s),ethanol and by-product yields (acetate and L-lactate) (Yp/s),and the doubling time (Td). Results showed that this strain wascapable of growing on minimal medium containing glucose orxylose as a single carbon source. This strain utilized glucose andxylose simultaneously (co-fermentation), although there wasglucose repression of xylose at relatively low glucose concentration(0.5% w/v), particularly when yeast extract (0.2% w/v) was addedto the medium. The highest biomass yield was obtained at 0.5g l-1 on glucose medium; the yield increased when yeast extractwas added (at 0.59 g l-1). The highest specific growth rate of 0.25was obtained in the phase I growth when the strain was grownon a mixture of glucose and xylose (0.5% : 0.5% w/v) medium.Diauxic growth was shown on the mixture of glucose, xylose,and yeast extract. The strain produced low level of ethanol (0.1g l-1), as well as low level (0.2 g l-1) of by-products (L-lactateand acetate) after 15 hours. The results suggests its potentialapplication for fermenting lignocellulosic agricultural wastes forethanol production.